Health Risk Assessment of Metal Contamination in Four Green Leafy Vegetables from Various Open Markets in Benghazi - Ahmida, Nagwa; Busaadiaa, Mariam; Towier, Najma; El-zwaey, Randa; Elferjani, Hawaa; Alzardomia, Reem; Ahmida, Mohemed (Journal of Pure & Applied Sciences, 2024)
This study analysed aluminium, essential metals (chromium, manganese, iron, nickel, copper and zinc), and toxic metals (lead and cadmium) in green leafy vegetables (arugula, mint, parsley, and spinach) obtained from various markets in Benghazi city. A flame Atomic Absorption Spectrometer was used to determine the metal contents. Hazard quotient (HQ) and hazard index (HI) calculations were employed to assess non-carcinogenic and carcinogenic risks associated with the metals in the vegetables. Results showed that aluminium was detected in only 50% of the samples. All vegetable samples contained manganese, iron, copper and zinc within the ranges of 1.072-6.87mg, 26.71-298.4mg, 1.00-3.45mg and 3.61-9.33mg per 1kg of vegetable dry weight, respectively. Nickel and chromium were found in 33% and 50% of the samples, respectively. Cadmium and lead were present in all samples except for two spinach and two parsley samples. The levels of essential metals in the samples were below the maximum allowable limits set by FAO-WHO regulations. However, the contents of nickel, cadmium and lead in some vegetable samples exceeded the maximum limits. The metal contents in the collected vegetables were mostly lower than reported results from previous international studies. The HQ and HI values for the analysed metals were all below unity, suggesting that the consumption of these selected vegetables as part of a daily diet poses no threat to human health.